Effect of Dipyrone, Naproxen and Diclofenac Potassium on Blood Cells (Revista Brasileira Multidisciplinar, 2009)
In therapy, nonsteroidal anti-inflammatory drugs (NSAIDs) are widely used to treat mild conditions and severe musculoskeletal disorders. However, some effects may occur due to their use, such as agranulocytosis, leukopenia and aplastic anemia. Objectives: to evaluate the effect of some NSAIDs on leukocyte production; to evaluate possible modification of the granules of neutrophils and to compare the total leukocyte count, by using manual and automated methods. 42 samples of whole blood of female rats, Wistar race, were analyzed in this experiment. The animals ingested solutions of diclofenac (DC), dipyrone (DP) and naproxen (NX), in two concentrations: the therapeutic plasma and another ten times more concentrated, for 5 days. We performed differential counts on stained smear and leukocytes were counted using manual methods with the Neubauer counting chamber and automated method (Coulter T-890). The comparison between the methods presented no significant differences in any analyzed group. Regarding to the overall number of leukocytes, no significant changes between the groups were observed. Regarding to the differential count we observed a significant increase in the number of atypical lymphocytes found in the group treated with diluted DP. This study demonstrated that dipyrone: 1) served as a toxic agent due to lymphocyte activation and the large number of neutrophils with nuclear pyknosis; 2) the Coulter T-890 can be used for total leukocyte count of animals; 3 ) other anti-inflammatory drugs studied did not cause abnormalities.
Keywords: Leukocytes; Agranulocytosis; NSAIDs; Dipyrone; Hematology